Correction: CuI assisted desulfurative Sonogashira reaction of mercapto N-heterocyclic derivatives with alkynes. Issue 53 (3rd July 2017) - Yang, Zan; Li, Jiao; Yang, Tao; Zhou, Congshan
Abstract : Correction for 'CuI assisted desulfurative Sonogashira reaction of mercapto N-heterocyclic derivatives with alkynes' by Zan Yang et al., RSC Adv., 2016, 6, 65775–65778.